Low vision rehabilitation program in myopic macular degeneration: a case report - Fernandes, Nádia (2023)
Introduction: Patients with high myopia are at risk of developing myopic macular degeneration (MMD), which leads to vision loss and irreversible visual impairment. Elderly populations are affected by loss of quality of life. Low vision services should offer specialized training programs to help patients overcome difficulties in daily living activities. This study aimed to describe the results of a low vision rehabilitation program (LVR) in a patient with MMD. Methods: A 69-year-old male patient with MMD was included in the LVR at an ophthalmology clinic in Portugal. The LVR had a length of 8 weeks and was divided into two phases. The first phase included the use of prisms for image relocation (IR) with eccentric viewing exercises to stabilize the preferred retinal locus. In the second phase, training with low-vision aids was performed. Best corrected visual acuity (BCVA) for distance and near, contrast sensitivity (CS), reading speed (RS) and face recognition were compared pre and post-rehabilitation. Additionally, the patient had open-angle glaucoma that was treated (glaucoma eye drops and neuroprotection treatment) and monitored by Spectral-domain optical coherence tomography.